Posterior reversible encephalopathy syndrome in a woman who used gonadotropin-releasing hormone agonists: a case report - Minhee Lee; Tae Hee Kim; Se Jeong Kim; Byung Chul Jee (Obstetrics & Gynecology Science, 2019)
Posterior reversible encephalopathy syndrome (PRES) is a newly described adverse effect possibly associated with gonadotropin-releasing hormone (GnRH) agonist therapy. We report a case of PRES after 2 doses of depot GnRH agonists in a 44-year-old woman with a huge myoma uteri and iron-deficiency anemia. Brain magnetic resonance imaging showed high signal lesions in both occipital lobes on fluid-attenuated inversion-recovery (FLAIR) images, compatible with PRES. After treatment with anticonvulsant, she recovered both radiographically and clinically. The association between PRES and GnRH agonist use is still enigmatic, and thus should be further clarified.